GENDER - CLAIRE COLEBROOK (NEW YORK PALGRAVE MACMILLAN, 2004)
Claire Colebrook places the term in its historical contexts and traces its development from the Enlightenment to the present, before moving on to the evolution of the concept of gender from within the various stances of feminist criticism, and exploring recent developments in queer theory and post-feminism.
Keywords: Gender Identity -- Sexual Orientation -- Feminist Theory